2008
DOI: 10.1002/ijc.23888
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglycerate kinase 1‐overexpressing lung cancer cells reduce cyclooxygenase 2 expression and promote anti‐tumor immunity in vivo

Abstract: In addition to the known function in the glycolytic pathway, phosphoglycerate kinase 1 (PGK‐1) promotes reduction of plasmin disulfide bonds leading to angiostatin formation and inhibition of tumor angiogenesis. In this study, the effects of PGK‐1 on anti‐ tumor immunity against lung cancer were evaluated using the Tet‐Off control of PGK‐1 expression in the Lewis lung carcinoma (LLC‐1). There was no significant difference in cell proliferation between parental LLC‐1 and LLC‐1 transduced with PGK‐1 (PGK‐LLC‐1).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 36 publications
0
34
0
1
Order By: Relevance
“…29 Moreover, in lung cancer cells, PGK1 overexpression reduced cyclooxygenase 2 expression, and decreased tumor growth and promoted anti-tumor immunity in vivo. 30,31 PGK1 can bind DNA, influencing DNA replication and repair in mammalian cell nuclei. 32,33 A proteomic analysis of glycolysis in lung cancer tissues revealed that poorly differentiated tumors had significantly lower PGK1 levels compared with moderate or well-differentiated tumors, indicating that PGK1 was down-regulated during lung cancer carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, in lung cancer cells, PGK1 overexpression reduced cyclooxygenase 2 expression, and decreased tumor growth and promoted anti-tumor immunity in vivo. 30,31 PGK1 can bind DNA, influencing DNA replication and repair in mammalian cell nuclei. 32,33 A proteomic analysis of glycolysis in lung cancer tissues revealed that poorly differentiated tumors had significantly lower PGK1 levels compared with moderate or well-differentiated tumors, indicating that PGK1 was down-regulated during lung cancer carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although PGK1 seemed to be a promising prognostic marker, its role in lung cancer is controversial. In fact, in a more recent study, overexpression of PGK1 was found to limit tumor growth in mice subcutaneously injected with the Lewis lung carcinoma cell line (LLC-1), by promoting antitumor immunity [34]. Moreover, LLC-1 cells overexpressing PGK1 showed lower invasion ability and a reduced angiogenesis induction.…”
Section: Prognostic Biomarkersmentioning
confidence: 99%
“…Some studies have established that bone marrow-derived MSCs can engraft injured tissues, such as those of the lung, liver, heart, and brain, and recover their function. In the past 10 years, certain institutional studies have confirmed that the use of stem cell transplantation is an important tool in the treatment of several types of malignancies (7)(8)(9). For these reasons (10), such cells are currently being tested for the potential use in cell and gene therapy for tumors (11,12).…”
mentioning
confidence: 99%